The problem of scientific terminology in the creative heritage of M. M. Bakhtin (by the example of the concepts «carnival», «laughter word» and «menippea») - Nikonov, Alexander N. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
This article is devoted to the problem of studying the philosophical and cultural heritage of M. M. Bakhtin, in particular his scientific terminology. The main difficulties faced by modern Bakhtin studies in the study and description of the terminological apparatus of the thinker are revealed. The features of M. M. Bakhtin’s scientific terminology and the specifics of its use in the scientist’s work, which are pointed out by most modern researchers, are analysed. Using the example of the analysis of the concepts of «carnival», «laughter word» and «menippea» in the works of Bakhtin scholars, a variety of approaches in the study and interpretation of the philosopher’s scientific terminology is shown.
Keywords: M. M. Bakhtin; Bakhtin studies; scientific terminology; Bakhtin contexts; carnival; laughter word; menippea